Elementy innowacyjne w funduszach strukturalnych krajów Grupy Wyszehradzkiej - Tuszyński, Kazimierz (Innovation Elements in Structural Funds of the Countries of Visehrad Group, 2006)
In this article author gives analytical presentations of innovation aspects of National Development Plans four Visegrad Countries(VC). Presents Operational Programs and structural funds allocation in all VC's pointed out measures dedicated for innovation and technology transfer activity in the end there are comparisons and conclusions.
Prace Naukowe Akademii Ekonomicznej we Wrocławiu; 2006; nr 1116, s. 638-645